2016
DOI: 10.5194/gmd-9-3137-2016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the boundary layer dynamics of the TM5 model over Europe

Abstract: We evaluate the capability of the global atmospheric transport model TM5 to reproduce observations of the boundary layer dynamics and the associated variability of trace gases close to the surface, using radon (222Rn), which is an excellent tracer for vertical mixing owing to its short lifetime (half-life) of 3.82 days. Focusing on the European scale, we compare the boundary layer height (BLH) in the TM5 model with observations from the NOAA Integrated Global Radiosonde Archive (IGRA) and in addition with ceil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…In contrast, pronounced enhancements in measured and simulated CH 4 compared to the background are apparent at the other three sites, especially in the lower ∼ 2 km due to regional emissions. These enhancements show some seasonal variation, with largest vertical extension during summer (∼ 2 km), while they are confined to the lower ∼ 1 km during winter due to the seasonal variations in the average boundary layer height (Koffi et al, 2016). Please note that the differences in the background mole fractions, which are visible in Fig.…”
Section: Evaluation Of Inverse Modelsmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, pronounced enhancements in measured and simulated CH 4 compared to the background are apparent at the other three sites, especially in the lower ∼ 2 km due to regional emissions. These enhancements show some seasonal variation, with largest vertical extension during summer (∼ 2 km), while they are confined to the lower ∼ 1 km during winter due to the seasonal variations in the average boundary layer height (Koffi et al, 2016). Please note that the differences in the background mole fractions, which are visible in Fig.…”
Section: Evaluation Of Inverse Modelsmentioning
confidence: 88%
“…A recent comparison of the TM5 BLH with observations from the NOAA Integrated Global Radiosonde Archive (IGRA) (Koffi et al, 2016) showed that TM5 reproduces the daytime BLH relatively well (within ∼ 10-20 %), but larger deviations were found for the nocturnal BLH, especially during summer, when very low BLHs (< 100 m) are observed. Here, we use only profiles for which the (TM5 diagnosed) BLH is not lower than 500 m. The average enhancement of the measurements and model simulations in the boundary layer compared to the background is denoted by c OBS, BL and c MOD, BL , respectively (further details about the evaluation of the enhancements are given in the Supplement).…”
Section: Evaluation Of Inverse Modelsmentioning
confidence: 99%
“…The extent to which NARR can simulate the features of PBL depth seasonal cycles over different sites characterized by various climate types observed in Figures 11 and 12 will provide new findings on the skill of reanalysis products. Thus, it will be possible to address in detail the effects of changes in land surface forcing over diverse geographical regions, as was recently performed by [42] for Europe using Transport Model 5 (TM5). Also, the analyses will be extended for the >200 IGRA sites located along coasts around the world to further investigate the impact of marine boundary layer features on PBL depths at coastal locations.…”
Section: Summary Conclusion and Outlookmentioning
confidence: 99%
“…In addition, errors caused by simulations of the boundary layer height in the transport model also must be considered in the future. The height of the boundary layer is a critical parameter in atmospheric transport models, since it controls the extent of the vertical mixing of trace gases emitted near the surface (Koffi et al, ).…”
Section: Discussionmentioning
confidence: 99%